2020
DOI: 10.1186/s40794-020-00113-3
|View full text |Cite
|
Sign up to set email alerts
|

“Universal test and treat” program reduced TB incidence by 75% among a cohort of adults taking antiretroviral therapy (ART) in Gurage zone, South Ethiopia

Abstract: Background: Tuberculosis (TB) remains the leading cause of morbidity and mortality in peoples living with HIV and at least 25% of deaths are attributed to TB. Many countries implement the Universal Test and Treat (UTT) program for HIV, which is believed to reduce the incidence of TB. However, there are limited studies that evaluate the impact of UTT on TB incidence. Therefore, by recruiting a cohort of ART users in the "UTT" and "differed treatment" programs, we aim to measure the effect of the UTT program on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…found to be 4.84 per 100 PY of observation. This finding is in line with studies conducted in the Gurage zone, Ethiopia (4.79cases per 100 PY), Arba Minch, Ethiopia (5.36 cases per 100 PY), and Tanzania (4.4 cases per 100 PY) [16][17][18]. However, it is higher than the studies from Brazil and the USA which reported the incidence of TB to be (2.28 cases per100 PY), and (0.7cases per 100PY), respectively [19,20].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…found to be 4.84 per 100 PY of observation. This finding is in line with studies conducted in the Gurage zone, Ethiopia (4.79cases per 100 PY), Arba Minch, Ethiopia (5.36 cases per 100 PY), and Tanzania (4.4 cases per 100 PY) [16][17][18]. However, it is higher than the studies from Brazil and the USA which reported the incidence of TB to be (2.28 cases per100 PY), and (0.7cases per 100PY), respectively [19,20].…”
Section: Plos Onesupporting
confidence: 92%
“…This variation could be explained by the difference in the study period. This means our study was done after the universal test and treat program and this might decrease the incidence [ 16 ] as a result of early initiation, strong follow up, and proper implementation in TB/HIV care service. Moreover, creation of better awareness regarding the prevention of TB/HIV co-infection might also contribute to the low incidence [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have reported the incidence of IO under the UTT policy. In Ethiopia, a reduction of TB incidence by 75% in the UTT programme compared to the deferred programme was observed [ 17 ]. The WCA are once more trailing the rest of SSA in documenting their experiences in implementing UTT.…”
Section: Introductionmentioning
confidence: 99%